Ocular dominance columns in New World monkeys - Livingstone, MS (J Neurosci, 1996)
Squirrel monkeys normally lack ocular dominance columns in V1. This study shows that squirrel monkeys can exhibit clear ocular dominance columns if they are made strabismic within a few weeks of birth. Columns were seen only in layer 4C beta and were coarser than the overlying blob pattern in the same animal. In physiological recordings from layer 4C of a normal squirrel monkey, single units were mostly monocular, but units driven by the two eyes were intermixed. These results suggest that in squirrel monkeys activity-dependent mechanisms do normally segregate geniculate inputs from the two eyes, but on a much finer scale than in Old World primates. Strabismic owl monkeys also showed ocular dominance columns; normal owl monkeys showed variable expression. Because ocular dominance columns, when present in New World monkeys, tend to occur in later-maturing parts of layer 4C, I hypothesize that a difference in the relative timing of the maturation of geniculocortical inputs and intracortical lateral connectivity explains the variability of ocular dominance column expression in New World monkeys.